AVAILABILITY AND ADEQUACY OF WATER, SANITATION AND HYGIENE (WASH) FACILITIES IN SECONDARY SCHOOLS - Olatunji, Rotimi Williams; Taiwo, Noeem Thanny (Journal of Environmental Science and Sustainable Development, 2021)
Hand-washing practice, which is globally recognized as the simplest, most affordable and effective way of curtailing the spread of infectious diseases, is still low in developing countries. This is largely influenced by the dearth and adequacy of Water, Sanitation and Hygiene (WASH) facilities. This paper investigated the level of availability and adequacy of WASH facilities in secondary schools in a developing, sub-Sharan country, particularly Lagos State, Nigeria. Protection Motivation Theory (PMT) guided this research. In all, 620 pupils were selected through multi-stage sampling methods. Two local government areas were selected from each of the three senatorial zones in the study area. Through purposive sampling method, Junior Secondary 3 (JS 3 or Basic 9), and Senior Secondary 3 (SS3) were selected from each local government of the State, comprising schools that are owned by Lagos State Government the others are privately owned. Research instruments adopted included questionnaire, focus group discussion guide, document observation and unobtrusive observation of hand hygiene facilities. Quantitative data were analyzed through the Statistical Package for Social Sciences (SPSS), while focus group data and related online media materials were analyzed based on research themes. Findings showed that majority of the respondents (87.4%) admitted that the most common type of toilet facility was a water closet, followed by a pit latrine (13.7%) and open space (1.6%) for defecation. Although respondents were on average satisfied with the level of provision of running water in secondary schools in Lagos State, the majority considered the provision of wash hand basin to be very inadequate. Researchers therefore recommend improvement of structures and facilities relating to WASH in schoolls throughout Lagos State, Nigeria.